2017
DOI: 10.1096/fj.201600951rrr
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: differentiation of stem cells into functional pericytes

Abstract: Pericytes are an integral cellular component of vascular structures. Numerous studies have investigated various stem cell types as potential sources of pericytes for application in cell-based therapy. The diverse stem cell types and variable experimental protocols of these studies make it imperative to evaluate the relevant scientific literature on the basis of a unified standard. The purpose of this systematic review is to rigorously evaluate the relevant scientific literature for conclusive evidence that ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…In contrast, although whole stem cell therapies could have more adverse side effects, they might have a stronger impact on neovascularization. Several researchers demonstrated that MSCs also differentiate into perivascular cells, in order to stimulate vessel maturation, which cannot be achieved by their associated paracrine EVs [75]. This differentiation potential should also be compared between DPSCs and BM-MSCs and taken into account when choosing the cell type and fraction for regenerative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, although whole stem cell therapies could have more adverse side effects, they might have a stronger impact on neovascularization. Several researchers demonstrated that MSCs also differentiate into perivascular cells, in order to stimulate vessel maturation, which cannot be achieved by their associated paracrine EVs [75]. This differentiation potential should also be compared between DPSCs and BM-MSCs and taken into account when choosing the cell type and fraction for regenerative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This is hampered by the heterogeneous characteristic of vascular PCs in the same tissue, as well as in vascular beds of different tissues, and lack of specific markers. 45 In this study, human fetal brain-derived PCs were purchased from ScienCell Laboratories (Carlsbad, CA). Cells were expanded and banked upon receipt for use over the duration of these studies.…”
Section: Methodsmentioning
confidence: 99%
“…The initial differentiation protocols for PC differentiation from human pluripotent stem cells (hPSCs), including human embryonic stem cells (hESCs) and hiPSCs, are based on spontaneous embryoid body formation. [101][102][103][104] While this protocol generated the cells expressing some PC markers (CD146, CD105, and PDGFRb), the yield was very low. Adapted from Rustenhoven et al 4 and Iendaltseva et al 120…”
Section: Pc Differentiation From Human Induced Pluripotent Stem Cellsmentioning
confidence: 99%